2(2a+3)=3(2a-1)+a

Simple and best practice solution for 2(2a+3)=3(2a-1)+a equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(2a+3)=3(2a-1)+a equation:


Simplifying
2(2a + 3) = 3(2a + -1) + a

Reorder the terms:
2(3 + 2a) = 3(2a + -1) + a
(3 * 2 + 2a * 2) = 3(2a + -1) + a
(6 + 4a) = 3(2a + -1) + a

Reorder the terms:
6 + 4a = 3(-1 + 2a) + a
6 + 4a = (-1 * 3 + 2a * 3) + a
6 + 4a = (-3 + 6a) + a

Combine like terms: 6a + a = 7a
6 + 4a = -3 + 7a

Solving
6 + 4a = -3 + 7a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-7a' to each side of the equation.
6 + 4a + -7a = -3 + 7a + -7a

Combine like terms: 4a + -7a = -3a
6 + -3a = -3 + 7a + -7a

Combine like terms: 7a + -7a = 0
6 + -3a = -3 + 0
6 + -3a = -3

Add '-6' to each side of the equation.
6 + -6 + -3a = -3 + -6

Combine like terms: 6 + -6 = 0
0 + -3a = -3 + -6
-3a = -3 + -6

Combine like terms: -3 + -6 = -9
-3a = -9

Divide each side by '-3'.
a = 3

Simplifying
a = 3

See similar equations:

| g/17=5 | | -5y=2/5 | | 20=-d+9 | | 6r^2-6r-36=0 | | 2x+y=14.40 | | 3(2n-6)=18 | | 2*9=t/5 | | (-24)-17=x | | 2a+12=8a-3 | | b+4/3=9 | | 10x-4(2x+7)=-12 | | b+3/-4=-16 | | 7(j-5)=-14 | | c/4=6+12 | | b+4/-5=-5 | | 6=v/9.6 | | 5x+7y=1000 | | 3bsquared=3 | | -55=.625r | | 4a-2a+11=5+5a | | 16=r/8 | | 15=-8+z/5 | | a+22=5 | | (6u^5+10(u^2)v^5)/8(u^5)y | | 6r^2-19r+15=0 | | 18w+50=284 | | 6x+8y=2200 | | -10x^2=-540 | | -25x=-6x+3+92 | | 6-5x+x=-10 | | a/5=35 | | 7x+6-5x=14 |

Equations solver categories